Tungsten extractive metallurgy: A review of processes and their challenges for sustainability. (October 2019) - Shen, Leiting; Li, Xiaobin; Lindberg, Daniel; Taskinen, Pekka
Graphical abstract: Highlights: Tungsten is a strategical and critical rare metal, its extraction intrinsically links to all supply chain stages. The current situations of tungsten concentrates and scraps are critically assessed. The history and development of tungsten extraction technology are reviewed in detail. The state of the art of the tungsten extraction technology is critically pointed out. The recommendation and improvement for tungsten extractive metallurgy are proposed. Abstract: Tungsten, as a strategic and critical raw material, has a wide range of industrial applications, due to its remarkable physical and chemical properties and the difficulty in finding a viable substitution. Tungsten extractive metallurgy produces the intermediate product from tungsten raw materials, intrinsically linking to the tungsten industry across the supply chain stages. This paper critically reviews the tungsten extraction technologies and their challenges for the sustainability of tungsten metallurgy. The extractive metallurgy of tungsten has developed for more than 150 years since 1847, and made a tremendous progress. The hydrochloric acid process is still used in the industrial production to produce pure tungstic acid and metatungstic acid nowadays, but it is limited by the formation of H2 WO4 product layer in the decomposition. The current commercial tungsten extractive metallurgy by soda/caustic soda digestion with solvent extraction or ion exchange step can use various raw materials and obtain the uniform and high-quality product with a better energy efficiency, less labor and higher tungsten yield. However, there also exist some disadvantages such as large amount of reagent consumption, absence of chemical recycle, and discharge of large volumes of high-salinity wastewater. The recently developed laboratory processes try to solve these problems, but some improvements are needed to increase the industrial applicability. The optimized industrial process needs an overall consideration of the adoption of increasingly complex raw materials, the recycle of aqueous solutions and chemicals, and the recovery of valuable substances in processing circuit, as well as the practical policy. This paper contributes to better understanding the tungsten extraction processes and developing a sustainable tungsten metallurgy in an environmentally friendly and economical way.